'Hoppers may strike here...Kill 'em with USDA-Recommended Toxaphene - Hercules Incorporated (1949 Hercules Advertisements, 1949)
Advertisement for Toxaphene, a synthetic organic insecticide toxicant developed by the Hercules Powder Company primarily for use in agricultural insecticides. The advertisement details predictions for an impending grasshopper infestation and includes a map of the United States highlighting areas forecast to feel the worst effects. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Toxaphene; Chemical industry; Hercules Incorporated; Insect pests--Control; Corporations; Naval stores; Insecticides; Advertising, Industrial; Insect pests